Cognitive distortions mediate the relationship between defense styles and depression in female outpatients - Turkcapar, Mehmet Hakan; Batmaz, Sedat; Kocbiyik, Sibel; Yalcinkaya-Alkar, Ozden (EUROPEAN JOURNAL OF PSYCHIATRY, 2016)
Background and Objectives: Some clinicians use different psychotherapeutic methods in combination in their practice. These combinations reflect the need for more rigorous research on the common pathways which these different therapy orientations may be utilizing, and one way to identify these pathways would be to investigate some core assessment tools or conceptual foundations of these two different approaches: Aim: The aim of the present study was to evaluate the relationship between defense mechanisms and cognitive distortions, and to identify the mediating role of cognitive distortions between defense styles and depression. Methods: A total of 342 female psychiatric outpatients aged 18 and older were recruited. A diagnostic interview and rating of the depression severity were undertaken, and the Cognitive Distortion Scales and the Defense Style Questionnaire were completed by the participants. Hierarchical regression analyses were conducted to test for the direct and indirect effects of the defense styles. Results: Cognitive distortions and defense mechanisms were both correlated with the severity of depression, but the correlations were stronger for the former. Conclusions: The findings are suggestive of the mediating effect of cognitive distortions between defense mechanisms and the severity of depression.
Keywords: Cognitive behavioral theory; Cognitive distortion; Defense style; Depression; Mediation analysis; Psychodynamic theory